2001
DOI: 10.1103/physreva.63.043613
|View full text |Cite
|
Sign up to set email alerts
|

Interference of a Bose-Einstein condensate in a hard-wall trap: From the nonlinear Talbot effect to the formation of vorticity

Abstract: We theoretically study the coherent expansion of a BoseEinstein condensate in the presence of a confining impenetrable hard-wall potential. The nonlinear dynamics of the macroscopically coherent matter field results in rich and complex spatio-temporal interference patterns demonstrating the formation of vorticity and solitonlike structures, and the fragmentation of the condensate into coherently coupled pieces. 03.75.Fi,05.30.Jp

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 33 publications
4
41
0
Order By: Relevance
“…Note that this is different from the way the box potential was constructed in Ref. [31], where a set of large-amplitude Gaussians was used. In essence, we mimic here an "exact" hard-wall potential where the BEC cannot tunnel −even slightly− through the wall.…”
Section: B Trapping Potential and Moving Obstaclementioning
confidence: 99%
See 2 more Smart Citations
“…Note that this is different from the way the box potential was constructed in Ref. [31], where a set of large-amplitude Gaussians was used. In essence, we mimic here an "exact" hard-wall potential where the BEC cannot tunnel −even slightly− through the wall.…”
Section: B Trapping Potential and Moving Obstaclementioning
confidence: 99%
“…However, our 2D al square box is achieved numerically by a different method than that of the latter authors. The main motivation of this work, then, is largely based on the latter work of Ruostekoski et al [31]. Additional motivation stems from a previous investigation by Jackson et al [1], who simulated the motion of an "object" through a dilute BEC in a 2D al harmonic trap, where the object (or obstacle) corresponds to a laser-induced vortex potential.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous paper [9] we studied the dynamics of a condensate inside a simple resonator (modelled by a one dimensional square box) and focused particularly on the influence of the inter atomic interactions on the behavior of the system. We showed that starting from a localized wave packet and by increasing the nonlinearities we pass from a quasi linear regime, where phenomena like nonlinear revivals and fractional revivals are expected [10], to a regime where stochastization of the movement takes place and where the nonlinear revivals of the wave packet are replaced by revivals of regular dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Vortices are familiar in systems with nonlinear interactions. Ruostekoski et al [14], as a theoretical example, found vortices in an expanding BEC reflecting from the hard walls of a two-dimensional (2D) circular box. Indeed, there are a variety of ways that vortices can be produced in nonlinear optics (see Ref.…”
Section: Introductionmentioning
confidence: 99%